Urgensi penerapan sistem pengendalian internal pada perbankan syari’ah - Gunawan, Risma (Maliki Interdisciplinary Journal, 2024)
This research examines the challenges of uncertainty in applying sharia principles in sharia banking, primarily due to various interpretations of Islamic law and differing sharia financial practices across countries. It explores the role of internal control systems in addressing this uncertainty and the impact of financial regulations on sharia compliance. The main findings reveal that internal control systems help Islamic banks ensure operational decisions align with sharia principles, manage compliance risks, and boost public trust. The growing role of technology in sharia banking increases risk complexity, necessitating stronger controls for data security and operational risks. Additionally, financial regulations that set sharia compliance requirements and sanctions for violations highlight the need for effective internal controls. This qualitative research uses a case study method, with data collected through evaluation and identification of articles, books, and research journals. The research objects are sharia banks, and the results indicate uncertainty in applying sharia principles, the significant impact of technology, and the influence of regulations on internal control systems in sharia banking.